Survival association of XRCC1 for patients with head and neck squamous cell carcinoma: A systematic review and meta-analysis - Fan Yang; Liuqing Zhou; Jingcai Chen; Yao Luo; Yanjun Wang (Frontiers in Genetics, 2023)
Background: Epidemiologic studies have demonstrated that X-ray repair cross-complementary group 1 (XRCC1) is one of the susceptibility factors in head and neck squamous cell carcinoma (HNSCC) patients. However, its clinical prognostic impact remains controversial. Thus, a meta-analysis was performed to clarify the association between XRCC1 and the survival outcomes in HNSCC patients.Methods: Following the Preferred Reporting Items or Systematic Reviews Meta Analyses (PRISMA) 2020 guidelines, literature searches were systematically performed in PubMed, EMBASE, Web of Science, Wanfang, and Chinese National Knowledge Infrastructure (CNKI) databases with manual retrieval. Hazard ratios (HRs) and 95% confidence intervals (CIs) were collected to estimate the correlation between XRCC1 and the survival outcomes of HNSCC patients.Results: Ten studies including 1995 HNSCC patients who satisfied the inclusion and exclusion criteria were included in this meta-analysis. Pooled analysis indicated that XRCC1 Arg399Gln and XRCC1 high protein expression were significantly correlated with poor overall survival with HR of 1.31 (95% CIs: 1.03-1.66, p = 0.027) and 2.32 (95% CIs: 1.55-3.48 p = 0.000) in HNSCC patients. In addition, our results demonstrated that XRCC1 was significantly associated with poor progression-free survival (HR = 1.42, 95% CIs: 1.15-1.75, p = 0.001) in HNSCC patients.ConclusionThis meta-analysis demonstrated that XRCC1 Arg399Gln and XRCC1 high protein expression increase the risk of poor survival for HNSCC patients. XRCC1 is a potential therapeutic target for HNSCC.